Nano High‐Entropy Materials: Synthesis Strategies and Catalytic Applications. Issue 2 (13th November 2020) - Li, Huining; Zhu, Han; Zhang, Songge; Zhang, Ning; Du, Mingliang; Chai, Yang
Abstract : High‐Entropy Materials In article number 2000033, Han Zhu, Mingliang Du, Yang Chai, and co‐workers overview the development of the synthesis strategies for various types of high‐entropy materials (HEMs), emphasize their formation mechanisms and illustrate their advantages and challenges. The superior catalytic behavior of HEMs compared with their traditional analogue materials in both thermal and electrocatalysis are discussed and the underlying structure‐activity correlation are revealed.